Review of the breeding status of birds in Rio Grande do Sul, Brazil - Maurício,Giovanni N. (2013)
Information on the breeding biology of birds is essential for improving avian life-history theory and implementing sound management and conservation actions for these organisms. Comprehensive reviews of this kind of information are lacking for most Neotropical regions, including Rio Grande do Sul, the southernmost Brazilian state. Aiming to update the knowledge on the reproductive status of birds in Rio Grande do Sul, we reviewed breeding records of all potential breeding species recorded in the state using a set of predefined, restrictive criteria for accepting breeding evidences as effective. Data satisfying our criteria were available for 165 species in the literature. We also collected novel breeding information obtained in the state for an additional 126 species, including observations for several species whose reproductive biology is poorly known. Among these are birds previously unknown to breed in Brazil. This new data and the critical review of the previous information resulted in a total of 291 species for which breeding evidences are accepted as effective. This corresponds to 54.7% of the 532 species considered either confirmed or potential breeders in the state. In addition to providing information on nesting dates, clutch size, nest architecture and breeding behavior of south Brazilian birds, our review serves as a benchmark for the adequate assessment of avian breeding records elsewhere. We hope to stimulate observers to rigorously document breeding events, especially for taxa for which basic information is lacking.